2022
DOI: 10.3389/fphar.2022.966486
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of prognosis between neoadjuvant imatinib and upfront surgery for GIST: A systematic review and meta-analysis

Abstract: Background: Significant survival benefit of adjuvant imatinib therapy has been observed in gastrointestinal stromal tumor (GIST). However, the impact of neoadjuvant imatinib on prognosis of GIST remains unclear. This meta-analysis aimed to compare the prognostic impact between upfront surgery and neoadjuvant imatinib plus surgery on GIST.Methods: A comprehensive literature search was performed to identify eligible studies up to 30 Sep 2021, through PubMed, Embase, Web of Science, and Cochrane Library. Studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…A systematic review conducted in August 2022 encompassing patients with rectal GISTs located throughout the gastrointestinal tract indicated that individuals who received imatinib therapy before surgical resection had improved overall survival rates compared with those who underwent surgical resection without prior chemotherapy. Nevertheless, the survival rates without disease were similar in both groups 19 …”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…A systematic review conducted in August 2022 encompassing patients with rectal GISTs located throughout the gastrointestinal tract indicated that individuals who received imatinib therapy before surgical resection had improved overall survival rates compared with those who underwent surgical resection without prior chemotherapy. Nevertheless, the survival rates without disease were similar in both groups 19 …”
Section: Discussionmentioning
confidence: 78%
“…Nevertheless, the survival rates without disease were similar in both groups. 19 In our case, after a multidisciplinary discussion with radiology specialists, we determined that excision of the mass with an intact capsule was feasible following a transanal wide excision. Due to the significantly elevated mitotic index, imatinib 400 mg/day was prescribed.…”
Section: F I G U R Ementioning
confidence: 90%
“…The study concluded that receiving imatinib therapy followed by surgical resection had better survival than the patients who underwent surgical resection without preceding chemotherapy. However, the disease-free survival in both groups was the same [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…This review focuses on these aspects of adjuvant therapy for GISTs. The neoadjuvant treatment of GISTs has been the topic of other recent reviews [24,25].…”
Section: Introductionmentioning
confidence: 99%